2017
DOI: 10.1007/s10544-017-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Probing of peripheral blood mononuclear cells anchoring on TNF-alpha challenged-vascular endothelia in an in vitro model of the retinal microvascular

Abstract: Retinopathy is a complication of diabetes that affects the eyes; it stems from damage to the microvasculature of the retina and eventually compromises vision. The diagnosis of retinopathy is difficult to make because there are no early symptoms or warning signs. Dysfunction of the retina's microvascular networks is believed to be associated with inflammatory cytokines and tumor necrosis factor alpha (TNF-α). To investigate the effect of these cytokines, such as TNF-α, a polydimethylsiloxane (PDMS)/glass hydrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, the XRD results show a distinct peak with 2q values of 15. 6 and 22.5 (marked with *) that are attributed to cellulose from all rice paper specimens and lens paper, conrming the similar degree of crystallization of cellulose within raw rice paper and lens paper (Fig. 1D).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the XRD results show a distinct peak with 2q values of 15. 6 and 22.5 (marked with *) that are attributed to cellulose from all rice paper specimens and lens paper, conrming the similar degree of crystallization of cellulose within raw rice paper and lens paper (Fig. 1D).…”
Section: Resultsmentioning
confidence: 87%
“…[4][5][6] The rst cell-based application of paper wherein a cell-in-gels-in-paper (CiGiP) model was developed by Dr Whitesides in 2009. 7 It was reported that the advantageous characteristic of paper, as a low-cost and abundant material to study 3D models, is that it can be stacked and de-stacked to reveal the inner 3D morphology.…”
Section: -3mentioning
confidence: 99%
“…Simultaneously, the local damaged blood vessels can produce a variety of cytokines, chemokines, and inflammatory mediators, such as platelet-derived growth factor, insulin-like growth factor, etc. [ 24 , 25 ]. Under the stimulus of these factors, a massive proliferation of smooth muscle cells causes neointimal hyperplasia and aggravates the pathological outcomes of vascular stenosis, which mainly promotes the pathophysiological process of AS.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that autophagy, i.e., mechanism to remove dysfunctional cell components, was significant for photoreceptor survival under hyperglycemic conditions [260]. It is noted that, while several microsystems have been developed to model diabetic retinopathy, these projects surprisingly neglect Müller glia and focus almost exclusively on endothelial cells [261][262][263]. Future microfluidic systems are needed to develop in vitro models of diabetic retinopathy and blood retinal barriers to advance regenerative treatments for vascular and metabolic eye diseases.…”
Section: Neuronal-glia Communicationmentioning
confidence: 99%